Association between handgrip strength, handgrip strength asymmetry, and anxiety in Korean older adults: The Korean National Health and Nutrition Examination Survey 2022 - Sang-Youn Choi; Su-Min Park; Eun-Cheol Park (PLoS ONE, 2025)
Low handgrip strength (HGS) and HGS asymmetry are associated with age-related physical and mental disorders in older adults. This study aimed to examine the association between HGS-related factors and anxiety to evaluate whether HGS assessments can assist in identifying anxiety risk. In total, 1,750 participants from the Korea National Health and Nutrition Examination Survey of 2022 were included in this study. Individuals whose HGS values were below the 20th percentile of the study population stratified by sex were classified into the low-HGS group. Anxiety was assessed using the generalized anxiety disorder with a 7-item scale. Multiple logistic regression was used to analyze the relationship between HGS level and asymmetry and anxiety, adjusting for covariates. Overall, 70 (8.7%) men and 123 (13.0%) women had anxiety. Elevated odds of anxiety were observed in older women with low HGS (adjusted odds ratio: 2.17, 95% confidence interval: 1.31–3.61). There was a positive correlation between the degree of asymmetrical HGS and anxiety among women. This study found positive associations between low HGS, HGS asymmetry, and anxiety in older Korean women. This population may require specific interventions to help maintain good mental health.